God over all divine aseity and the challenge of Platonism - Craig, William Lane 1949- (2016)
God Over All: Divine Aseity and the Challenge of Platonism is a defense of God's aseity and unique status as the Creator of all things apart from Himself in the face of the challenge posed by mathematical Platonism. After providing the biblical, theological, and philosophical basis for the traditional doctrine of divine aseity, William Lane Craig explains the challenge presented to that doctrine by the Indispensability Argument for Platonism, which postulates the existence of uncreated abstract objects. Craig provides detailed examination of a wide range of responses to that argument, both realist and anti-realist, with a view toward assessing the most promising options for the theist. A synoptic work in analytic philosophy of religion, this groundbreaking volume engages discussions in philosophy of mathematics, philosophy of language, metaphysics, and metaontology
Introduction -- God : the sole ultimate reality -- The challenge of Platonism -- Absolute creation -- Divine conceptualism -- Making ontological commitments (1) -- Making ontological commitments (2) -- Useful fictions -- Figuratively speaking -- Make-believe -- God over all
Hier auch später erschiene, unveränderte Nachdrucke
Keywords: God (Christianity); Creation; Mathematics -- Philosophy